LAW ENFORCEMENT AGAINST DEFAMATION UNDER THE ELECTRONIC INFORMATION TECHNOLOGY LAW: A Case Study of Decision No. 658/Pid.Sus/2021/PN.Sby - Amirullah, Muhammad Iqbal; Sholehuddin, Dr. M.; Rijadi, Prof. Dr. Prasetijo (Acitya Wisesa: Journal of Multidisciplinary Research, 2024)
The ITE Law is considered as a strong legal basis to control social media and regulate information technology, as stipulated in Law No. 11/2008 and its amendment in Law No. 19/2016. This law applies to anyone, both at home and abroad, if their actions harm the interests of Indonesia. Consumer protection is an important aspect of the modern economy to ensure equitable and ethical practices in the marketplace. This research discusses the concept of consumer protection in the context of consumer rights in Indonesia and how such protection is applied in an ever-evolving market. The main focus of this research is how the ITE Law handles defamation from a legal perspective. Using a normative juridical approach, this research examines relevant legislation, legal literature, and court decisions. This research examines legislation, legal literature, and relevant court decisions. In practice, ITE Law often faces challenges, such as differences in interpretation of articles that have the potential to limit freedom of speech as well as debates over the line between criticism and defamation. The results indicate that even though the ITE Law provides a clear legal basis, its implementation is still a cause for controversy. A balance is needed between the protection of individual reputation and freedom of expression. Regulatory reform and increasing legal awareness in the community are important steps to ensure a fairer and more effective application of the ITE Law.